Association of computed tomography scores to psychophysical measures of olfaction: A systematic review and meta‐analysis. Issue 2 (14th July 2022) - Chen, Tiffany; Chidarala, Shreya; Young, Gabrielle; Jeong, Seth S.; Nguyen, Shaun A.; Edwards, Thomas S.; Schlosser, Rodney J.
Abstract: Background: While various sinus computed tomography (CT) scoring systems have been proposed and used in the literature, no single system has been identified as superior. The strength of associations between CT scoring systems and measures of olfaction also remains unclear. Methods: A systematic review of PubMed, CINAHL, Scopus, and the Cochrane Library was conducted following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Studies that reported both CT scores and measures of olfaction in a cross‐sectional manner were included. Results: A total of 37 studies were eligible for meta‐analysis. Of 8035 patients with chronic rhinosinusitis, 55.6% were male patients and 53.2% had chronic rhinosinusitis with nasal polyps. Analysis by meta‐regression was performed of Lund‐Mackay (LM) versus Smell Identification Test‐40 (SIT‐40; 12 studies), Brief Smell Identification Test (BSIT; 10 studies), Sniffin' Sticks (SS; 10 studies), and Toyota & Takagi (T&T) olfactometry (four studies). A significant moderate association was found between LM and SIT‐40 ( R 2  = 0.612, p  < 0.001) and LM and SS ( R 2  = 0.612, p  < 0.001). An association between LM and BSIT approached significance ( R 2  = 0.461, p  = 0.054). No significant associations were noted between LM and T&T olfactometry and between LM and SS when stratified by nasal polyp status. Conclusion: There is a significant moderate association of current CT scoring systems to SIT‐40 and SS. Further research should focus on associations of objective measures of olfaction to CT scores of the nasal cavity, sinuses, and olfactory cleft, as well as other disease markers.